Pendampingan Komunitas Petani Kopi di Desa Jatiarjo Kecamatan Prigen Kabupaten Pasuruan - Mulyono Wibisono; Budi Santoso; Fafit Rahmat Aji; Diyono Yusuf; Sareh Rudianto (LPPM Universitas Yudharta Pasuruan, 2020)
Jatiarjo village has tourism potential well known to many people; moreover, this village is one of the buffer villages or recharge area areas in Pasuruan district. Besides tourism, the business in Jatiarjo village is coffee agribusiness. Each business actor runs his own business, and there is no institutional link between them, even though the activities they carry out are functionally interrelated. Such a business structure is not conducive to developing a sustainable coffee agribusiness business due to the absence of a harmonious and harmonious functional relationship between agribusiness actors, so market dynamics cannot always be responded to efficiently. The purpose of this assistance is to increase the income of coffee farmers, which quality and productivity can still be improved. The implementation of this service activity is carried out through Participatory Action Research, emphasizing community empowerment of coffee farmer groups as partners. The results of this mentoring generally stated that coffee farmers in Jatiarjo village received many benefits during this mentoring which in the end, they became more aware of coffee cultivation and processing